PENGARUH IKLAN TERHADAP LOYALITAS MEREK YANG DIMEDIASI OLEH KETERLIBATAN PELANGGAN DAN KEPERCAYAAN MEREK PADA PENGGUNA SCARLETT WHITENING - Raihanum Putri; Syarifah Evi Zuhra (Departemen Manajemen, 2023)
This study aims to measures the Effect of Advertisement on Brand Loyalty mediated by Customer Engagement and Brand Trust to Scarlett Whitening Users. The sample used in this study was the users of Scarlett Whitening, amounting to 210 respondents. The sampling technique used is purposive sampling. Structural Equation Modeling (SEM) was used as an analytical method to determine the effect between the variables involved. Based on the result of the SEM analysis, it was identified that advertisement affect brand loyalty, advertisement affect customer engagaement, advertisement affect brand loyalty, customer engagement affect brand loyalty, brand trust affect brand loyalty, customer angagement partially mediates the affect of advertisement on brand loyalty, and brand trust partially mediates the effect of iklan to brand loyalty.